Guidance Note on the Fund's Transparency Policy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The global financial crisis has had a significant impact on low-income countries (LICs)' debt vulnerabilities. Recent debt sustainability analyses (DSAs) indicate that external and fiscal financing requirements have increased. In addition, standard measures of a country's capacity to repay debt?GDP, exports, and fiscal revenue?are expected to be permanently lower. On average, debt ratios are therefore expected to deteriorate in the near term, particularly for public debt.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: PP; Publication; Regime; Staff